Thinking in new boxes a new paradigm for business creativity - Brabandere, Luc de; Iny, Alan (Random House, 2013)
Outlines a new model of practical creativity that challenges business professionals to evaluate customers, goals, and companies in engaging alternative ways, explaining how to develop strategies for effective and adaptive business environments.